(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
The field of regulation of construction at the European Union level is complex and it encompasses standardisation at several levels by various stakeholders in the system. Namely, construction regulatory systems are the work of various European Union institutions and European standardisation organisations (European Committee for Standardization and European Committee for Electrotechnical Standardization). Precisely this fact may lead to specific misalignments of the system itself thereby jeopardizing legal certainty as well as physical safety of citizens. Therefore, this paper aims to present regulations in the field of construction at the European Union level, placing an emphasis on individual standards of the above standardisation organisations, and discuss problems attached to regulation at multiple levels. The aforementioned instances and European standardisation organisations regulate construction products, works, professional qualifications of stakeholders in the system, occupational safety and health, environmental impact etc. and therefore the paper provides a review of sources of law which exist at the European Union level in the ambit of construction – regulations and decisions of appropriate European Union bodies – and significance of Eurocodes as standards. In terms of contents, these documents are related to regulation of the field of a technical nature and technical rules. Therefore, awareness and application of these sources of law is important because the general design itself and its components, as parts of documentation submitted in special administrative proceedings to obtain a construction licence, for instance in the Republic of Croatia, must be aligned with the aforementioned sources of law. Such alignment contributes to the principle of lawfulness and ultimately to legal certainty in the procedure to obtain a construction licence. This paper employs, with the purpose of a scientific approach to this topic, analyses and syntheses as well as inductive and deductive methods to research the theoretical part of the paper. A part of results obtained through an empirical research conducted for the purpose of development of a doctoral thesis is also analysed in this paper and descriptive statistical methods are used within the framework of this analysis. The analysis of the results reviews the degree of use of the European Union sources of law in procedures to obtain construction and operating licences in the Republic of Croatia. The discussion employs logical and teleological methods of interpretation. Recommendations for improvements to the system considering a part of the analysed empirical research results are provided accordingly within the concluding considerations.